2017
DOI: 10.1111/jcpp.12751
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and pathways of language and motor development in four prospective cohorts of young children in Ghana, Malawi, and Burkina Faso

Abstract: BackgroundPrevious reviews have identified 44 risk factors for poor early child development (ECD) in low‐ and middle‐income countries. Further understanding of their relative influence and pathways is needed to inform the design of interventions targeting ECD.MethodsWe conducted path analyses of factors associated with 18‐month language and motor development in four prospective cohorts of children who participated in trials conducted as part of the International Lipid‐Based Nutrient Supplements (iLiNS) Project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
80
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 39 publications
14
80
4
2
Order By: Relevance
“…Although this is the first study to describe child development in a MAM population, our findings concur with a prospective study among 4,205 children in Ghana, Malawi, and Burkina Faso, where identified predictors of motor and language development included linear and ponderal growth, Hb, and iron status (Prado et al, ). A strong association between linear growth and development was also seen in this MAM population, where HAZ was the strongest anthropometric correlate of motor and language development.…”
Section: Discussionsupporting
confidence: 88%
“…Although this is the first study to describe child development in a MAM population, our findings concur with a prospective study among 4,205 children in Ghana, Malawi, and Burkina Faso, where identified predictors of motor and language development included linear and ponderal growth, Hb, and iron status (Prado et al, ). A strong association between linear growth and development was also seen in this MAM population, where HAZ was the strongest anthropometric correlate of motor and language development.…”
Section: Discussionsupporting
confidence: 88%
“…Similar significant associations between LAZ and motor development, and LAZ and language development, have been reported in a study of children 5-19 months of age living in Zanzibar (Olney et al, 2009). Direct associations between linear growth and motor and language development have also been reported in a study of children from Ghana, Malawi, and Burkina Faso (Prado et al, 2017). Strength, muscle mass, and endurance are important in children 6-24 months of age who are learning to crawl, walk, and run (Adolph, Vereijken, & Denny, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…A weak, but significant, direct or indirect (through motor development) association with hemoglobin was observed for language, personal-social development, and memory. Others have also reported significant associations between hemoglobin and motor development (Olney et al, 2009(Olney et al, , 2013Prado et al, 2017). Research in Chilean children showed that greater severity of anemia and duration of anemia of more than 3 months was associated with decreased psychomotor development scores (Walter, 1989).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations